Target-site resistance to glyphosate in Eleusine indica biotypes from South Sulawesi and Lampung, Indonesia - Lazuardi, Ahmad Nur; Kurniadie, Denny; Umiyati, Uum; Widianto, Ryan (Universitas Padjadjaran, 2026)
Glyphosate is a non-selective systemic herbicide that has been widely used to control weeds by local corn farmers in South Sulawesi and Lampung Provinces of Indonesia. However, some corn farmers in these two regions were considered that glyphosate herbicide at the standard field dose no longer effective against goosegrass (Eleusine indica). To confirms the level of its resistance to glyphosate, seeds of E. indica suspected to be glyphosate-resistant were collected from corn fields in Soppeng Regency-South Sulawesi and South Lampung Regency-Lampung (designated as GR-1 and GR-2 respectively), along with a known susceptible biotype from Sumedang Regency-West Java (GS) as a comparison. By using whole-plant pot assay method in a greenhouse at the Ciparanje. A range of seven glyphosate concentrations was applied to the seedlings at the Experimental Farm, representing 0, 0.25, 0.5, 1, 2, 4, and 8 x the standard field rate. Dose–response experiment showed that GR-1 and GR-2 biotypes has a low levels resistance to glyphosate (2.57 and 2.96 folds of each) compared to susceptible biotype (GS). Sequencing results confirmed the Pro-106-Ser mutation in the EPSPS genes of the resistant biotypes. This specific amino acid substitution is among the most frequently documented mechanisms of resistance in weed species. Therefore, the shared mutation in the GR-1 and GR-2 biotypes likely confers this resistance. These findings serve as an early warning for corn farmers to manage and prevent further spread of E. indica glyphosate-resistant biotypes.